Allergen‐specific basophil reactivity exhibits daily variations in seasonal allergic rhinitis. Issue 3 (22nd December 2014) - Ando, N.; Nakamura, Y.; Ishimaru, K.; Ogawa, H.; Okumura, K.; Shimada, S.; Nakao, A.
Abstract It remains poorly understood how symptoms in allergic rhinitis are most severe during overnight or early in the morning. The circadian clock consisting of a network of several 'clock genes' including Clock drives daily rhythms in physiology. This study showed that allergen‐induced surface CD203c expression on basophils in seasonal allergic rhinitis caused by Japanese cedar pollen exhibited a time‐of‐day‐dependent variation associated with temporal variations in canonical circadian clock gene expression. We also found that bone‐marrow‐derived basophils (BM basophils) generated from wild‐type mice exhibited a time‐of‐day‐dependent variation in IgE‐mediated IL‐4 and histamine production, which was not observed in BM basophils generated from Clock‐mutated mice. Therefore, allergen‐specific basophil reactivity shows daily variations depending on the circadian clock activity in basophils, which could partly explain temporal symptomatic variations in allergic rhinitis. Additionally, circadian variations in CD203c expression should be considered for interpretation of this biomarker in clinical research.